Investigation as a means of the parliamentary control over government actions - سكر, حسين محمد (Journal of Legal Sciences, 2019)
Parliamentary investigation is one of the most important means of the parliament in its oversight on the work of the government. It is different from other types of investigations carried out by the Parliament itself, such as electoral or legislative investigation. It is also different from the investigation conducted by the administration or courts. This investigation is been conducted by a committee which consisted of some of members of parliament. The committee is looking to search the truth in a case related to the public interest and for that it usually has powers to access documents relevant to the case under investigation. Moreover, it has the right to request the presence of any government official before it. The committee usually performs its job in secret and temporarily, as they have to complete their work during a period of time that varies from state to state.At the end of the investigation, the committee will send a report to the parliamentary includes the results and recommendations. The recommendations are limited to specific matters. It either recommend to fill a legislative gap that was the cause of the violation or referring the incompetent officials and government employees in the event of proven crimes or violations of the laws to the courts to take appropriate measures against them.The Parliamentary investigation may reach a serious outcome that threatens the presence of the Minister or the Government as a whole and entails raising the political responsibility of the Government and raising the issue of confidence in the event that the parliamentary investigation committee proves the minister or the government in some of the areas of activity that the Commission investigated.However, the investigation may end with the recommendation that there is no violation and that no party can be held responsible for the failure of the investigative committee to find any evidence that could condemn the government.  In this case, the recommendation does not exceed the government's warning that necessary measures should be taken to prevent any irregularities in some of the activities that it undertakes or supervises. The committee recommends renewing confidence in the government because there are no violations committed by it.